Barriers to implementing poverty alleviation through livelihood strategies: A participatory analysis of farming communities in Ethiopia's upper Blue Nile basin. Issue 136 (October 2022) - Alemie, Tilashwork C.; Buytaert, Wouter; Clark, Julian; Tilahun, Seifu A.; Steenhuis, Tammo S.
Abstract: Poverty is multi-dimensional global challenge that impedes individual and community capacities to satisfy basic needs. These capacities are shaped by locally configured institutional and biophysical processes that are often hidden from external researchers and practitioners. To explore this worldwide aspect, we adopt participatory rural appraisal (PRA) methods to expose barriers to implementing livelihood strategies to address poverty in Ethiopia's upper Blue Nile basin, where 85 % of the population are subsistence farmers reliant on local ecosystem services (ES). We identify local barriers to poverty alleviation in three steps. First, we classify major ES-livelihood interrelationships among communities of Debre Mawi catchment in upper Blue Nile. Secondly we assess ongoing struggles in these interrelations using combined biophysical and social assessment criteria to evaluate how poverty relates to current patterns of ES management. The analysis identifies complex interdependencies between livelihoods and regulating (crop pest controls), provisioning (water, land, and feed availability, soil fertility) and cultural (top-down ES management, population growth) ES that create bottlenecks to effectively 'lock in' poverty. Thirdly, we identify potential new ES management strategies, focused on dry season water availability. We conduct participatory field experiments on rooftop water harvesting to show this is a promising approach for increasing water availability to enhance agricultural production. Depending on the rooftop area, our modelling suggests that farmers can improve household income by US$136– 14, 876 from 5 months beef fattening and US$69–7704 from 4 months sheep fattening. Except these specific livelihood strategies, the findings are replicable to the world's ES-dependent regions. Highlights: A novel rigorous approach was developed to maximize poverty alleviation. Water scarcity is most important bottleneck to move out of poverty. Rooftop water harvesting avoids water scarcity and improves livelihood. Unpredictable rainfall causes significant crop yield reduction. Poverty alleviation needs to focus on the poorest segment of society.